Electrical wiring residential : based on the 1990 national electrical code - Mullin, Ray C. (Albany, New York : Delmar Publishers Inc., 1990)
This best selling, comprehensive text focuses on the technical skills required to safely perform domestic electrical wiring installations. Code rules, theory, electrical calculations, wiring methods and problem-solving are combined to guide students step-by-step-through a complete wiring.
Includes index.
Keywords: ELECTRICAL WIRING, INTERIOR